THE PATHOGENIC EFFECTS OF STAFF TURNOVER IN GOVERNMENT TERTIARY INSTITUTIONS IN MANICALAND IN ZIMBABWE - Makande, E; Whatmore, Chikwature (Top Educational Review Journal (TERJ), 2023)
This study was on the pathogenic effects of staff turnover in government tertiary institutions in Manicaland Province. Forty five purposively sampled respondents took part in this study -15 respondents from each of the three tertiary institutions. Qualitative research paradigm was employed and a case study research design was used. Focus group discussion was employed as the data gathering tool. The qualitative data gathered was presented using descriptive analysis using emerging themes. The study concluded that bad relationship between the administration and the lecturer fuelled the staff turnover at Government Tertiary Institutions because of these issue employees feels insecure in terms of Job security. Factors mentioned for retaining staff in tertiary education institutions weren't taken care of. The recommendations were that it is vital for colleges to have in mind that retention plans and indeed programs need Tertiary Education Institutions overhaul, comprehensive and thoughtful method to be effective. This is because most staff retention plans are expensive and vary across colleges and also they need substantial effort to make them work. The relationship between the lecturers and administrators should be improved so as to get the best from the two groups to contribute towards organisational goals efficiently. To enlighten the matter regarding staff leaving, actions have to be taken as these programs compete for talent to keep the main valuable individuals within the organisation, it's becoming common to give staff retention bonuses in most educational institutions.